Evaluasi Efektivitas dan Efisiensi Sistem Informasi Operasional menggunakan Metode Cost Benefit Analysis: Studi Kasus pada Restaurant Sea Food di Jakarta - Lianawati Christian; Ribka Rosalina; Melissa Melissa; Rosalia Rosalia (ComTech: Computer, Mathematics and Engineering Applications, 2013)
This study aims to identify whether the information system used by a sea food restaurant has been efficient and effective. It can support decision making for follow-up actions. The methodology used in this study is literature study, interview, and survey. To evaluate the effectiveness of operational information systems at the restaurant, we use cost benefit analysis. To evaluate whether the operational information system is efficient, we use questionnaire with Likert scale calculations. Based on the evaluation of the effectiveness and efficiency ofoperational information system at the restaurant, it can be seen there is a difference between investment in 2004-2009 and investment in 2010. From the results of calculation using cost benefit analysis to determine the effectiveness, we find that investment in 2004 was positive while investment in 2010 is still negative. Based on the results of questionnaires, the investments are considered efficient. Based on the evaluation, information systems used in sea food restaurant has been effective and efficient. The return on investment only takes less than two years and the information systems supports operational activities.